1988
DOI: 10.1159/000234518
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IgE Antibodies to a Wide Range of Insect Species in Subjects with Suspected Inhalant Allergies to Insects

Abstract: Sera obtained from subjects diagnosed on the basis of case history and skin tests as having inhalant allergies to insects, were tested for the presence of IgE antibodies to antigens from the house fly Musca domestica, a blowfly Calliphora stygia, the common clothes moth Tineola bisselliella, warehouse moth Ephestia cautella, cockroach Blattella germanica, carpet beetle Anthrenus verbasci and silverfish Ctenolepisma longicaudata. Approximately one-third of the sera reacted with extracts from all seven species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 4 publications
2
57
0
1
Order By: Relevance
“…No homologous cross-reactive component was observed in the cod, a vertebrate species. These data suggest that arginine kinases represent a novel class of invertebrate cross-reactive pan-allergens which may be implicated in the induction and maintenance of respiratory and food allergy in polysensitized patients (10,36). …”
Section: Discussionmentioning
confidence: 86%
“…No homologous cross-reactive component was observed in the cod, a vertebrate species. These data suggest that arginine kinases represent a novel class of invertebrate cross-reactive pan-allergens which may be implicated in the induction and maintenance of respiratory and food allergy in polysensitized patients (10,36). …”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, by immunofluorescence microscopy on shrimp, muscle staining was observed. The finding, in several studies, that many mite-positive sera reacted with insects [1] or Crustacea [6], suggested that the sera contained cross-reacting antibodies. In this study we identified tropomyosin as a cross-reactive allergen.…”
Section: Discussionmentioning
confidence: 99%
“…This observation in dicated the presence o f a cross-reactive antigen in mite, shrimp and insects. In the literature it has been suggested that there are cross-reacting IgE antibodies against mite, in sects and Crustacea [1][2][3][4][5][6]. Invertebrates are known to be strong sensitizers for IgE-mediated immune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antibodies could be cross-reacting antibodies originating from immune response against various insect antigens derived via inhalant or alimentary routes. Supporting this as sumption, Baldo and Panzani [23] have recently shown IgE cross-reactivity between different airborne insect allergens in humans.…”
Section: Discussionmentioning
confidence: 66%